(untitled) (Physical Education, Health and Social Sciences, 2025)
Background The fascia beneath the foot is called plantar fascia. It helps in the support of arch of foot and on bearing weight it under tension. Plantar fasciitis is an inflammation of thick tissue which is plantar fascia present on the base of foot that play role in causing heel pain, pain under the foot, metatarsalgia and other disabilities. Objective: The object of this study was to measure the effectiveness of active myofascial trigger point release and the kinesio taping VS conventional physiotherapy treatment of planter fasciitis for pain management. Methodology: This Study design was RCT. Study was conducted in as per availability area, institute and hospital. The 36 patient both male and female recruited for this study. Scales that were used included Foot Function Index Scale, Plantar fasciitis pain/disability scale. They were randomly divided into two groups. Experimental group treatment was having only myofascial trigger point release and kinesiotaping treatment only. Group A control group treatment: - Control group was set to fall under the regular conventional treatment that is heating therapy, cold therapy, ultrasound and infrared varying upon the patient severity. Group B experimental treatment: - Experimental group went under only myofascial Tigger point release also with kinesio taping treatment only. Results: Paired sample test used for the group analysis of four pairs compared, pre and post foot function index, pre and post VAS (PEPS) and pre and post planter fasciitis pain scale shows significance difference in each control and experiment group. Kinesio taping and myofascial trigger point release is better than conventional treatment for planter fasciitis pain management. Conclusion: Experimental group treatment show more effective results as compare to conventional treatment group.